Entre paisagens sulinas: fotografias para criação de novos mundos possíveis - Azevedo, Cláudio Tarouco de (Paralelo 31, 2021)
Ensaio visual do artista brasileiro Cláudio Azevedo que contrasta fotografias da paisagem sulina no Brasil. Palavras-chave: Paisagem sulina. Fotografia. Educação ambiental. Arte e meio ambiente. Between Southern Landscapes: Photographs for creating new possible worlds Abstract: Visual essay by the Brazilian artist Cláudio Azevedo which contrasts photographs depicting the landscape in southern Brazil. Keywords: Southern landscape. Photography. Environamental education. Art and Environment.